Efectos del Sars CoV 2 en Cavidad Bucal en Pacientes con Implantes Dentales. Scoping Review - Pacheco Uparela, Miguel Andrés; Pantoja Lazo, Jessica Andrea; Salas Vargas, Lizbeth Daniela; Tovar Marin, Natalia Strip (Universidad Antonio Nariño, 2023)
Covid-19 is a disease caused by the SARS-CoV-2 virus,approximately 400 billion infections have been reported, the mortality rate is around 6 million, its rapid spread generated the need to obtain knowledge about the signs and symptoms of patients, especially evaluating treatments such as dental implantology.